Tumor cell-based vaccine contributes to local tumor irradiation by eliciting a tumor model-dependent systemic immune response - Remic, Tinkara; Sersa, Gregor; Levpuscek, Kristina; Lampreht Tratar, Ursa; Ursic Valentinuzzi, Katja; Cör, Andrej; Kamensek, Urska (Frontiers in Immunology, 2022)
Introduction: Multimodal treatment approaches, such as radio-immunotherapy, necessitate regimen optimization and the investigation of the interactions of different modalities. The aim of this study was two-fold. Firstly, to select the most effective combination of IR irradiation and the previously developed tumor cell-based vaccine and then to provide insight into the immune response to the selected combinatorial treatment. Methods: The study was performed in immunologically different murine tumor models: B16F10 melanoma and CT26 colorectal carcinoma. The most effective combinatorial treatment was selected by comparing three different IR regimens and three different vaccination regimens. We determined the local immune response by investigating immune cell infiltration at the vaccination site and in tumors. Lastly, we determined the systemic immune response by investigating the amount of tumor-specific effector lymphocytes in draining lymph nodes. Results: The selected most effective combinatorial treatment was 5× 5 Gy in combination with concomitant single-dose vaccination (B16F10) or with concomitant multi-dose vaccination (CT26). The combinatorial treatment successfully elicited a local immune response at the vaccination site and in tumors in both tumor models. It also resulted in the highest amount of tumor-specific effector lymphocytes in draining lymph nodes in the B16F10, but not in the CT26 tumor-bearing mice. However, the amount of tumor-specific effector lymphocytes was intrinsically higher in the CT26 than in the B16F10 tumor model. Conclusions: Upon the selection of the most effective combinatorial treatment, we demonstrated that the vaccine elicits an immune response and contributes to the antitumor efficacy of tumor irradiation. However, this interaction is multi-faceted and appears to be dependent on the tumor immunogenicity.